Laboratory mouse models for bartonella bacterial infection: bacteremia, host specificity, and pathology - Colton, Leah, author; Foy, Brian, advisor; Michael, Kosoy, advisor; Gage, Kenneth L., committee member; Bowen, Richard, committee member (Colorado State University. Libraries, 2011)
Bartonella bacterial species are globally distributed in a diverse variety of mammalian reservoir hosts. Natural host infections are generally characterized by persistent bacteremias of long duration, seemingly without adverse host effect, whereas non-natural host infections can produce mild, self-limiting illnesses or more severe disease such as endocarditis. Incidental host infections seem to most closely resemble natural host infections when the taxonomic distance between the two hosts is small. The greater the taxonomic distance between the host of origin and the incidental host, the more likely it seems that the incidental host will either clear the bacteria or develop pathology following exposure. This level of bacterial host specificity has been demonstrated consistently and presents an enormous obstacle to the development of animal models, particularly murine models that reproduce characteristics of natural host infection or pathology consistent with human incidental infections. In this dissertation laboratory mouse models for bartonella infection are described following the introduction and literature review (Chapter 1). Chapter 2 reports infection of mice with bartonella strains from wild Mus species, simulating a cross-species host switch for the bacteria. Infected mice exhibited characteristics consistent with reports of natural rodent host infection. Chapter 3 reports on a mouse infection study using four rat bartonella strains, simulating a cross-genus host switch for the bacteria. Only one of the strains infected mice and alterations in bacteremia duration and magnitude were observed relative to those reported for natural host infections. Mice also displayed organ pathology following bacteremia resolution. Chapter 4 presents a mouse infection study using an Asian house shrew Bartonella elizabethae strain inoculated into three different laboratory mouse stocks. Mice of all three stocks developed bacteremia following bacterial exposures, a demonstration of cross-order host switching by the bacteria. No obvious differences in infection response were observed among the mice despite differences in their genetic backgrounds. Chapter 5 describes inoculation of aged mice with either a mouse bartonella strain or human Bartonella tamiae strains. Mice infected with the mouse strain developed bacteremia, whereas mice infected with B. tamiae did not, consistent with the idea that taxonomic distance between host of origin and incidental host can be a predictor of infection outcome. Chapter 6 details results of a study where aged mice were exposed to three different B. tamiae strains. The mice developed disease consistent with reports of human illness symptomatology. In summary (Chapter 7), these laboratory mouse models are presented as defined, scientific resources for research on Bartonella species host ecology, bacteria: host interactions, and transmission dynamics.
Keywords: bacteremia; bartonella; host specificity; infectious dose; mouse model; pathology